High Protein Intake Is Associated With Histological Disease Activity in Patients With NAFLD. Issue 5 (26th March 2020) - Lang, Sonja; Martin, Anna; Farowski, Fedja; Wisplinghoff, Hilmar; Vehreschild, Maria J.G.T.; Liu, Jinyuan; Krawczyk, Marcin; Nowag, Angela; Kretzschmar, Anne; Herweg, Jens; Schnabl, Bernd; Tu, Xin M.; et al.
Abstract : Overconsumption of carbohydrates and lipids are well known to cause nonalcoholic fatty liver disease (NAFLD), while the role of nutritional protein intake is less clear. In Western diet, meat and other animal products are the main protein source, with varying concentrations of specific amino acids. Whether the amount or composition of protein intake is associated with a higher risk for disease severity has not yet been examined. In this study, we investigated associations of dietary components with histological disease activity by analyzing detailed 14‐day food records in a cohort of 61 patients with biopsy‐proven NAFLD. Furthermore, we used 16S ribosomal RNA gene sequencing to detect associations with different abundances of the gut microbiota with dietary patterns. Patients with definite nonalcoholic steatohepatitis (NAFLD activity score of 5‐8 on liver biopsy) had a significantly higher daily relative intake of protein compared with patients with a NAFLD activity score of 0‐4 (18.0% vs. 15.8% of daily protein‐based calories, P  = 0.018). After adjustment for several potentially confounding factors, a higher protein intake (≥17.3% of daily protein‐based calories) remained associated with definite nonalcoholic steatohepatitis, with an odds ratio of 5.09 (95% confidence interval 1.22‐21.25, P  = 0.026). This association was driven primarily by serine, glycine, arginine, proline, phenylalanine, and methionine. A higher protein intake correlated with a lower Bacteroides abundance and an altered abundance of several other bacterial taxa. Conclusion: A high protein intake was independently associated with more active and severe histological disease activity in patients with NAFLD. Further studies are needed to investigate the potential harmful role of dietary amino acids on NAFLD, with special attention to meat as their major source.